Addressing the Challenges in dental practice during Covid-19: A review - Gupta, Sumeet; Gupta, Swati; Jagtap, Rohan D. (Journal of Advances in Internal Medicine, 2020)
Covid-19 was declared as global pandemic by WHO. World is not unknown to the family of coronaviruses due to previous epidemic caused by SARS and MERS. Healthcare professions have from time to time change their ways of practicing because of the direct threat posed by such infections, capable of causing human to human transmission. This article, based on our experience and guidelines issued by CDC as well as IDA, intends to provide a review of recommended protocols for dental professionals.